Guest Pro-environmental Behavior Towards the Implementation of Energy Efficiency through Smart Key Technology in Capsule Hotel - Anastasya Connietha Bagio; Lexi P. Budidharmanto (CV. Literasi Indonesia, 2023)
The purpose of this study was to determine guest pro-environmental behavior on the application of energy efficiency in capsule hotels with case studies in Bobobox Indonesia and Digital Airport Hotel. The method used in this research is qualitative analysis. The samples used were two capsule hotel management informants in Indonesia, namely Bobobox Indonesia and Digital Airport Hotel. The method used is purposive sampling. Data collection techniques in this study were carried out by online interviews through Zoom meetings and observations. Based on the results of data analysis, it can be concluded that the implementation of energy efficiency through smart key technology in capsule hotel improves the pro-environmental behavior of the guests. It can be observed through the willingness of guests to use the smart key technology implemented by the company. This study contributes to the field by exploring the impact of energy-efficient measures, particularly through the implementation of smart key technology, on guest pro-environmental behavior in the hospitality industry. The findings offer valuable insights for both businesses aiming to enhance sustainability in accommodations and travelers seeking to make eco-conscious choices while on the move.